2011
DOI: 10.4161/jig.1.1.14592
|View full text |Cite
|
Sign up to set email alerts
|

Is there a place for sedationless colonoscopy?

Abstract: REVIEW REVIEWUnsedated colonoscopy is available on a routine basis in many parts of the world.1 This paper will discuss the components of patient time burden of sedation, 2 tabulate the extent and significance of sedation-related complications 3 and review how various options without routine sedation impact these events in the context of colorectal cancer screening and surveillance. In the end we shall address the question in the title of this manuscript if there is a place for sedationless (unsedated) colonos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…2,3 Where it is available, conscious sedation has become standard, and even adopted for screening cases. Deep sedation enhances efficiency, but also markedly increases cost.…”
Section: Biographymentioning
confidence: 99%
“…2,3 Where it is available, conscious sedation has become standard, and even adopted for screening cases. Deep sedation enhances efficiency, but also markedly increases cost.…”
Section: Biographymentioning
confidence: 99%
“…Since the water method [1][2][3][4][5][6][7][8][9] and use of chromoendoscopy [10][11][12][13][14] were reported to have beneficial impacts, a performance improvement project evaluating their utility was carried out at the Sacramento VA Medical Center in Mather, California. Data were collected prospectively to monitor performance and analyzed retrospectively.…”
Section: Methodsmentioning
confidence: 99%
“…The water method has recently been reported to be superior to air method [1][2][3][4][5][6][7][8][9] , produces less sedation medication requirement in the sedated veterans [1][2][3] , and minimizes discomfort and enhances cecal intubation in the unsedated veterans [4][5][6] . Retrospective review of data in sedated veterans showed that the water method increased adenoma detection rate (ADR).…”
Section: Introductionmentioning
confidence: 99%
“…9 Unsedated colonoscopy offered to patients who consume the purge solution and arrive without an escort and do not object to having the colonoscopy done without sedation is the only unscheduled option. In community 31 and VA 32 practice settings 1-2% of colonoscopy patients are managed in this manner.…”
Section: Options Of Colonoscopy With and Without Routine Sedationmentioning
confidence: 99%
“…The in- creasing interest in the use of deep sedation for colonoscopy even in Korea, 8 possibly as a consequence of the recognition that unsedated colonoscopy can be uncomfortable, highlights the importance and timeliness of this review, in drawing attention to the use of the water method for colonoscopy in CRC screening and surveillance. Parts of this review were presented as a Keynote address 9 and two separate State of the Art lectures.…”
Section: Introductionmentioning
confidence: 99%